An Approach Based on Ford-Fulkerson Algorithm to Optimize Network Bandwidth Usage - Pinto Neto, Euclides; Callou, Gustavo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
Ford-Fulkerson algorithm is widely used to solve maximum Graph-Flow problems and it can be applied to a range of different areas, including networking. This paper proposes an approach based on Ford-Fulkerson algorithm to maximize the flow (bandwidth usage) of computer network. Such method mitigates congestion problems and increases network utilization. In order to show the applicability of the proposed approach, this paper presents the analysis of different network scenarios.